Pulsed Dilution Method for the Recovery of Aggregated Mouse TNF-α - Merat Mahmoodi; Maryam Ghodsi; Malihe Moghadam; Mojtaba Sankian (Reports of Biochemistry and Molecular Biology, 2017)
Background: The expression of mouse tumor necrosis factor alpha (TNF-α) in Escherichia coli is a favorable way to get high yield of protein; however, the formation of cytoplasmic inclusion bodies, which is the consequence of insoluble accumulated proteins, is a major obstacle in this system. To overcome this obstacle, we used a pulsed dilution method to convert the product to its native conformation. Methods: Reducing agent and guanidine hydrochloride were used to solubilize inclusion bodies formed after TNF-(α) expression. Then, the refolding procedure was performed by pulsed dilution of the denatured protein into a refolding buffer. The properly-folded protein was purified by metal affinity chromatography. Results: SDS-PAGE showed a 19.9 kDa band related to the mature TNF-(α) protein. The protein was recognized by anti-mouse TNF-(α) on western blots. The final concentration of the purified recombinant TNF-(α) was 62.5 μg/mL. Conclusions: Our study demonstrates the efficiency of this method to produce a high yield of folded mature TNF- (α).